UPAYA MENINGKATKAN EFEKTIVITAS BELAJAR LEMPAR TURBO DENGAN MENGGUNAKAN MEDIA MODIFIKASI TURBO SEDEHANA - sudarsinah (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of the study was to determine the extent to which the Modified Turbo Simple media could increase the effectiveness of learning discus throwing in class VI SDN Jejangkit Timur. The research was conducted at SDN Jejangkit Timur. The population of this study were all 6th grade students of SDN Jejangkit Timur consisting of 12 male students and 10 female students enrolled in the 2017/2018 academic year. The research method is Classroom Action Research, in this research activities are carried out in the form of a research cycle. Each cycle consists of four main activities, namely planning, action, observation, and reflection, it can be seen that the first cycle of activity reaches 70%, then in the second cycle it reaches 85%, this means that there is an increase of 15% after treatment or improvement in the second cycle, so that the average the average student activity for two cycles is 75%. Referring to the indicator of student activity for two cycles, 75% has active criteria. In other words, students during the turbo throwing lesson with the simple turbo modification media move actively, either when they get assignments from the teacher or on their own initiative. The average learning completeness for the final attitude aspect reaches 85% of the boys. and girls reached 72.5%